(untitled) (Biological Sciences - PJSIR, 2008)
The study investigated the effect of sublethal concentrations (39.10, 19.55, 9.87 and 0.00 mg/l) of Portland cement powder in solution on the electrolyte reserves (sodium, potassium, calcium, chloride and inorganic phosphorus) in the serum, liver and kidney of the juvenile African catfish Clarias gariepinus after a 15 day exposure period. The basic function of the determined electrolyte reserves in the body lies in controlling fluid distribution, intra and extra cellular acidobasic equilibrium, maintaining osmotic pressure of body fluid and normal neuro-muscular irritability. The result revealed significant (P<0.05) changes in serum sodium, potassium, calcium and chloride and insignificant (P>0.05) changes in inorganic phosphorus. Sodium, calcium, chloride and inorganic phosphorus and potassium were significantly (P<0.05) and insignificantly (P>0.05) different in liver and kidney, respectively. Ipso-facto, the effector organs viz: liver and kidney of teleost species – Clarias gariepinus which are primarily responsible for regulating water and ionic movement between external and internal milieu of fishes are susceptible to deleterious effects of Portland cement powder thus sublethal concentration (39.10 mg/l) of Portland cement powder in solution after a 15 day exposure has been most toxic and debilitating to the test fish.